Language activities in a minority–majority language context: book-reading at home is more important for Frisian than for Dutch. Issue 2 (18th March 2020) - BOSMA, Evelyn; BLOM, Elma
Abstract: Previous research has shown that in a minority–majority language context, the quantity of language input at home is more important for the development of the minority language than for the development of the majority language. In the current study, we examined whether the same holds true for the frequency of specific language activities at home. In a group of five- and six-year-old Frisian–Dutch bilingual children ( n = 120), we investigated to what extent vocabulary and morphology knowledge were predicted by reading activities, watching TV, and story-telling activities in both languages. The results showed that reading in Frisian predicted both Frisian vocabulary and morphology, while reading in Dutch only predicted Dutch vocabulary. This shows that reading at home is most important for the development of the minority language. This especially holds true for the acquisition of Frisian morphology, a domain that is known to be vulnerable in language acquisition.